Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Heavy silicon isotope and mass-independent mercury isotope fractionation signals of Archean TTGs: Insights into the recycling of the silicified oceanic crust in the source region - Xiao Hu; Wenbin Zhu; Haizhen Wei; Runsheng Yin; Yongxiang Li; Yiwei Rong; Di Chen (Chemical Geology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Bioavailability, Migration, and Accumulation Characteristics of Heavy Metals in the Soil–Lotus Root System Adjacent to Highways - Qiang Hu; Rong-hua Qiu; Ren-chao Zhu; Manisha Parajuli; Si-jie Wen; Zi-yang Sun; Ai-hua Yu (International Journal of Environmental Research, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Exploring spinal degenerative diseases therapy targets through druggability genes: a Mendelian randomization study - Hao Qin; Mingyu Hao; Zhitan Wang; Jing Zhang; Minghao Xie; Yuhang Diao; Xiaojun Hu; Hongtao Rong; Tao Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A Galactose-Modified Light-Activatable Persulfurated Arene Fluorescent Probe for Targeted Imaging of Polarity and Viscosity in Liver Cancer Cells - Pan-Xin Ge; Yan Rong; Lu-Lu Sun; Yuqing Hu; Xianzhi Chai; Hai-Hao Han; Liangliang Zhu (Journal of Fluorescence, 2026)

Numerical simulation of fracture propagation and interwell frac-hit mechanism in deep shale gas infill wells - Yufeng Wang; Qiang Wang; Jinzhou Zhao; Yongquan Hu; Jianglong Wang; Juhui Zhu; Rong Wang; Xiaowei Li; Yu Yang (Engineering Geology, 2026)

Morphology and ultrastructure of the proventriculus in the mole cricket Gryllotalpa orientalis Burmeister, 1838 (Orthoptera: Gryllotalpidae) - Bai-Long Yang; Ling Zhu; Ya-Rong Gu; Huan Hu; Ying Miao (Arthropod Structure & Development, 2026)

Isolation, Genome Sequencing and Proteomic Analysis of a LiCl-Tolerant Bacillus rugosus E-4 Strain from East Taijinar Salt Lake on the Qinghai-Tibet Plateau - Rong Xu; Sha Du; Zihua Liu; Miaomiao Hu; Jianlan Wu; Hongxia Zhu (Current Microbiology, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

High-efficiency and rapid photocatalytic degradation of rhodamine B and tetracycline by BiOBr nanosheets under simulated solar light - Rong Wang; Weikun Zhu; Jiayi Hu; Siyang Liao; Cheng Chen; Baihang Chen; Shaobin Huang; Jiangyao Chen (Journal of Environmental Sciences, 2026)

Study on diagnosis of subclinical mastitis and identification of pathogens using electronic nose detection of cow’s milk - Fang Wang; Yujun Zhu; Enqiu Zhang; Rong Zhang; Hongwei Duan; Shuai Yang; Xianghong Du; Xingxu Zhao; Xiaofei Ma; Lihong Zhang; Junjie Hu (Computers and Electronics in Agriculture, 2026)

Phosphate-modified attapulgite for efficient Pb(II) and Cd(II) removal: surface functionalization and adsorption mechanisms - Xinyao Zhang; Rong Yang; Wenxia Zhu; Di Meng; Xuanjie Huang; Zulin Wang; Bo Ma; Jun Yao; Wenjihao Hu (Environmental Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A novel strategy for controlling nitrite accumulation in fermented cabbage by regulating microbial community structure via cold plasma - Lin Zhu; Mengke Cheng; Yuan Wang; Xinyu Hu; Rong Wang; Biyue Yang; Xiang Xiao; Wei Wei (Food Control, 2026)

Reducing the Discrepancy in Quantifying the Temperature Dependence of Global Wetland Methane Emission - Han Hu; Ke Xue; Yishen Sun; Qing Zhu; Hans K. Carlson; Ruiwen Hu; Rong‐Xi Tan; Chao Qian; Weigen Huang; Jizhong Zhou; Jingdong Mao; Thomas W. Crowther; et al. (Global Change Biology, 2026)
Understanding the apparent temperature dependence of wetland methane emissions ( E M ) is critical for predicting climate‐carbon feedbacks, yet current estimates remain constrained by observational limitations and methodological inconsistencies. The inherent biogeographic heterogeneity of wetland ecosystems combined with sparse, unevenly distributed flux measurements introduces substantial uncertainty in characterizing spatial patterns of E M . This knowledge gap impedes accurate projections of wetland methane contributions under climate warming scenarios. Here, we develop a framework that integrates mixed‐effects models with artificial intelligence techniques to resolve scale‐dependent patterns in methane emission thermodynamics across global wetlands. Our unified framework demonstrates that only 73.6% (5th–95th quantiles: 71.8%–75.4%) of the global wetland area conforms to classical Arrhenius‐type temperature dependence. This framework can predict 69.5% (67.9%–71.1%) of the global wetlands with high confidence using the Mahalanobis distance and area of applicability tests. We quantify the weighted mean E M across high‐confidence predictable areas of 0.694 eV, with latitudinal differentiation: tropical (0.634 eV), temperate (0.678 eV), and boreal (0.745 eV) wetlands exhibit progressively stronger temperature responses. Ignoring these biogeographic variations could result in underestimation of projected end‐century methane emissions by 4.2%–13.3% across selected socioeconomic pathway scenarios. Our study refined the temperature sensitivity parameter in coupled climate‐carbon cycle models, thereby enhancing predictive accuracy of future global warming trends and informing strategic responses to climate change mitigation.

Sustainable bipolar membranes with three-dimensional flower-like spherical MgAl-layered double hydroxides doped quaternized chitosan for accelerated water dissociation and durability - Ming Li; Jinyun Xu; Hongze Li; Xiaoqing Wang; Shijie Shang; Xiaoyan Wang; Sijia He; Yanyan Ji; Li Yang; Rong Kuang; Chenxin Hu; Wenju Zhu; et al. (Desalination, 2025)

A durable immuno-protective core-shell microgel for the enhanced pancreatic islet transplantation in diabetes therapy - Zeming Hu; Yang Luo; Muhammad Junaid; Rong Xu; Yaoqi Chen; Jie Yao; Renhao Ni; Tong Zhu; Hua Zhang; Huiqing Ding; Yabin Zhu (Chemical Engineering Journal, 2025)

Cytochrome P450-mediated biotransformation of octocrylene in Tetradesmus obliquus: Integrative insights from transcriptomics, proteomics, molecular docking, and density functional theory calculation - Jun-Jie Hu; Chang-Gui Pan; Xiang-Rong Xu; Feng-Jiao Peng; Shan Liu; Jiying Pei; Zhen-Zhu Liu; Hao Liang; Kefu Yu (Journal of Hazardous Materials, 2025)

Yolk-dual shell structured dielectric-magnetic SiO2@C@void@Ni3ZnC0.7/C microspheres for boosting microwave absorption - Wei Ling; Peng Liao; Jiawei Zhu; Jianxin Wu; Caiwei Hu; Xianke Zhang; Jujun Yuan; Zuzhou Xiong; Xiurong Zhu; Chuicai Rong (Chemical Engineering Journal, 2025)

Enhanced atrazine mineralization using periphyton pretreated with zero-valent iron-activated peroxydisulfate - Huibin Niu; Qian Tao; Rong Zhu; Haitao Li; Yonglin Chen; Yu Hu; Zuliang Chen; Yonghong Wu; Yingping Huang; Cilai Tang (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Insights into Leuconostoc-clade as starters in Chinese paocai: Shaping microbial communities for rapid, safe, and flavor-preserving fermentation - Xinyu Hu; Mengke Cheng; Meng Zhang; Biyue Yang; Rong Wang; Juan Bai; Jiayan Zhang; Wei Wei; Lin Zhu; Xiang Xiao (Food Bioscience, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Thermosensitive poly (NVCL-co-GelMA) nanogels as a delivery platform for rectal administration of 5-ASA in ulcerative colitis - Rongjiao Sun; Limei Zhu; Xianzhu You; Rong Chen; Jiante Li; Rongrong Pan; Yueqi Jin; Hua Zhou; Ying Tan; Jiajia Dong; Wanle Hu (Chemical Engineering Journal, 2025)

Paleoproterozoic orogenic event in the western North China Craton: Insights from zircon U-Pb-Lu-Hf isotopes and geochemistry of meta-supracrustal rocks in the Beidashan complex, Alxa block - Yi-Wei Rong; Wen-Bin Zhu; Xi Wang; Jun-Yue Zhu; Xiao Hu (Precambrian Research, 2025)

Efficient uranium(VI) recovery from fluorinated wastewater via deferiprone ligand complexation - Juanlong Li; Yezi Hu; Zewen Shen; Huihui Jin; Rong He; Wenkun Zhu; Guixia Zhao; Zhuoyu Ji; Bin Ma; Xiangke Wang (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Precipitation patterns strongly affect vertical migration and methylation of mercury in legacy contaminated sites - Xujun Liang; Zhi-Cheng Hu; Yu-Rong Liu; Cunbin Gao; Yi Zhang; Yun-Yun Hao; Lijie Zhang; Jiating Zhao; Lizhong Zhu (Water Research, 2024)

Biological nitrogen fixation in paddy soils is driven by multiple edaphic factors and available phosphorus is the greatest contributor - Tianlong HU; Yanhui ZHANG; Hui WANG; Haiyang JIN; Benjuan LIU; Zhibin LIN; Jing MA; Xiaojie WANG; Qi LIU; Hongtao LIU; Zhe CHEN; Rong ZHOU; et al. (Pedosphere, 2024)

Integrative transcriptomic analysis reveals a broad range of toxic effects of triclosan on coral Porites lutea - Hao Liang; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Rong-Gui Zhu; Chao-Yang Zhou; Zhen-Zhu Liu; Kefu Yu (Journal of Hazardous Materials, 2024)

A compound heterozygous mutation of ERCC8 is responsible for a family with Cockayne syndrome - Meng-Wei Liu; Cheng-Feng Hu; Jie-Yuan Jin; Rong Xiang; Liang-liang Fan; Ya-Li Li; Lei Zhu (Molecular Biology Reports, 2024)

The effect of mixed microbial agents on tobacco black shank disease - Fang Liang; Chai Yunxia; Li Yuanyuan; Geng Shaowu; Bu Yunhong; Hu Yang; Ai Kebiao; Shi Jianfei; Duan Jiyou; Yang Maosong; Zhu Rong (Physiological and Molecular Plant Pathology, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Mitigation of malondialdehyde-induced protein lipoxidation by epicatechin in whey protein isolate - Wenhua Yao; Xingya Hao; Zhangjie Hu; Zhenghao Lian; Yue Cao; Rong Liu; Xiaoying Niu; Jun Xu; Qin Zhu (Food Chemistry, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Location-dependent occurrence and distribution of metal-based nanoparticles in bay environments - Siying Ying; Ziyi Liu; Yongrong Hu; Rong Peng; Xiaoshan Zhu; Shuofei Dong; Dong Yan; Yuxiong Huang (Journal of Hazardous Materials, 2024)

Preparation, characterization, and coating effect of bio-active nano-emulsion based on combined plant essential oils on quality of grass carp fillets - Mingtao Yang; Yunshan Zhu; Tianhao Ying; Jianhua Rong; Pengkai Wang; Yang Hu (Food Chemistry, 2024)

Rapid adsorptive removal of emerging and legacy per- and polyfluoroalkyl substances (PFASs) from water using zinc chloride-modified litchi seed-derived biochar - Zhen-Zhu Liu; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Hong-Ming Tan; Rong-Gui Zhu; Chao-Yang Zhou; Hao Liang; Kefu Yu (Bioresource Technology, 2024)

Simultaneous determination of trace marine lipophilic and hydrophilic phycotoxins in various environmental and biota matrices - Chao-Yang Zhou; Chang-Gui Pan; Feng-Jiao Peng; Rong-Gui Zhu; Jun-Jie Hu; Kefu Yu (Marine Pollution Bulletin, 2024)

Xylem adjustment and growth response of early- and late-successional tree species to rapid warming - Zihao Hu; Liangjun Zhu; Shuguang Liu; Pifeng Lei; Rong Zhang; Paolo Cherubini (European Journal of Forest Research, 2024)
Climate changes have dramatically affected forest succession. However, how trees at different successional stages respond to climate warming is unclear in the subtropics. Here, we compared the radial growth (RW) and xylem features of the early-successional stage Castanea mollissima and late-successional stage Quercus fabri in subtropical forests and assessed their response to climate changes. All parameters, including RW, number of vessels (VN), vessel density (VD), mean (MVA) and total (TVA) vessel area, percentage of conductive area within xylem (RCTA), theoretical (Kh) and xylem-specific (Ks) hydraulic conductivity, except for MVA of C. mollissima were significantly higher than those of Q. fabri . During the drought period, a notable adverse correlation between two cluster parameters of Q. fabri , associated with hydraulic safety and efficiency, suggested a pronounced hydraulic trade-off in Q. fabri under drought conditions. Castanea mollissima was more sensitive to climate and more prone to hydraulic failure than Q. fabri . Temperatures and moisture conditions positively and negatively affected the hydraulic efficiency-related parameters of C. mollissima . Moisture conditions in the previous summer and winter were significantly negatively and positively related to the radial growth of both species. The impact of generalized warming was not evident due to variations in hydraulic strategies and species characteristics, trade-offs between non-growing and growing season climates, and specific competition. If climate warming continues, C. mollissima growth will probably significantly decline due to the increasing risk of hydraulic failure. Warming may accelerate species replacement and forest succession in the study area by changing their lifespans and competitive relationships.

Stochastic community assembly of abundant taxa maintains the relationship of soil biodiversity-multifunctionality under mercury stress - Shuai Du; Xin-Qi Li; Li Bi; Dong Zhu; Hang-Wei Hu; Xiuli Hao; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Soil Ecology Letters, 2024)

Histopathological analysis of the wall enhancement of the spinal dural arteriovenous fistulae’s draining veins - Xiaojun Hu; Yuhang Diao; Zhenghao Hao; Mingyu Hao; Minghao Xie; Hongtao Rong; Tao Zhu (Acta Neurologica Belgica, 2024)

Comparative analysis of process selection and carbon emissions assessment of innovative steelmaking routes - Botao Xue; Guangsheng Wei; Yanze Hou; Hang Hu; HongJin Zhang; Rong Zhu; Kai Dong; Chao Feng; Lingzhi Yang; Hongbin Wang (Journal of Cleaner Production, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Photo-enhanced nanozyme with self-cascade catalysis enhances peroxidase-like activity for alcohol discrimination - Rina Su; Yu Wu; Weiqing Xu; Rong Tan; Ying Qin; Runshi Xiao; Canglong Wang; Liuyong Hu; Wenling Gu; Hongcheng Sun; Chengzhou Zhu (Chemical Engineering Journal, 2024)

27-Hydroxycholesterol inhibits trophoblast fusion during placenta development by activating PI3K/AKT/mTOR signaling pathway - Xiaoyan Zhao; Xiaxia Cai; Haiyan Zhu; Qinyu Dang; Qian Yang; Yandi Zhu; Yadi Zhang; Mengling Zhang; Xinyin Jiang; Zhuo Hu; Yuchen Wei; Rong Xiao; et al. (Archives of Toxicology, 2024)

Parabens and their metabolite in a marine benthic-dominated food web from the Beibu gulf, South China Sea: Occurrence, trophic transfer and health risk assessment - Rong-Gui Zhu; Chang-Gui Pan; Feng-Jiao Peng; Chao-Yang Zhou; Jun-Jie Hu; Kefu Yu (Water Research, 2024)

Characteristics of labile organic carbon fractions under different types of subsidence waterlogging areas in a coal mining area: A case study in Xinglongzhuang Coal Mine, China - Yanhua Fu; Zhenqi Hu; Qi Zhu; Ying Rong (CATENA, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

Tree-ring data reveal trees are suffering from severe drought stress in the humid subtropical forest - Rong Zhang; Zihao Hu; Paolo Cherubini; David J. Cooper; Liangjun Zhu; Pifeng Lei (Forest Ecology and Management, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The elements identification and model construction of rural tourism experience based on user-generated content - Zhongyuan Zhu; Rong Wang; Jing Hu (Environment, Development and Sustainability, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

New insights into sulfur input induced methylmercury production and accumulation in paddy soil and rice - Yunyun Li; Nali Zhu; Wenjun Hu; Yu-rong Liu; Wen Jia; Guoming Lin; Hong Li; Yufeng Li; Yuxi Gao; Jiating Zhao (Journal of Hazardous Materials, 2023)

Natural polymer Nicandra physaloides (L.) Gaertn seed gum mediated assembly of hydroxyapatite assembly as versatile sponge for water pollution control - Xudong Wu; Yazhou Wang; Li Zhou; Chengkun Cai; Mingfang Hu; Xiaofang Yu; Rong He; Wenkun Zhu (Journal of Cleaner Production, 2023)

In-depth profiling of di(2-ethylhexyl) phthalate metabolic footprints in rats using click chemistry-mass spectrometry probes - Yu-Ning Hu; Jin-Tao Zhan; Pei-Rong Bai; Na An; Jun-Jie Tan; Yan-Zhen Wang; Quan-Fei Zhu; Yu-Qi Feng (Journal of Hazardous Materials, 2023)

Effects of fuel injection and energy efficiency on the production and environmental parameters of electric arc furnace -heat recovery systems - Bohan Tian; Guangsheng Wei; Hang Hu; Rong Zhu; Hao Bai; Ziming Wang; Lingzhi Yang (Journal of Cleaner Production, 2023)

Screening of pesticides in serum, urine and cerebrospinal fluid collected from an urban population in China - Ke-Xin Zhao; Ming-Yan Zhang; Dan Yang; Rong-Shu Zhu; Zi-Feng Zhang; Ying-Hua Hu; Kurunthachalam Kannan (Journal of Hazardous Materials, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Alkali-catalyzed hydrothermal oxidation treatment of triclosan in soil: Mechanism, degradation pathway and toxicity evaluation - Yushuang Chen; Rui Shi; Hongjun Luo; Rong Zhang; Yafei Hu; Haijiao Xie; Neng-min Zhu (Science of The Total Environment, 2023)

Galvanic replacement reaction-regulated photoelectric response and enzyme-mimicking property of ionic liquid functionalized Cu@Cu2O aerogels for dual-mode immunoassay - Jinli Li; Hengjia Wang; Mingwang Liu; Ying Qin; Rong Tan; Liuyong Hu; Wenling Gu; Chengzhou Zhu (Chemical Engineering Journal, 2023)

Ultra-thin and highly flexible silver fractal dendrite/polyvinylidene fluoride composite film for efficient electromagnetic interference shielding - Zuomin Lei; Jianhong Wei; Zhiqiang Lin; Tao Zhao; Yougen Hu; Pengli Zhu; Rong Sun (Chemical Engineering Journal, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Occurrence, distribution, and ecological risk of organophosphorus flame retardants and their degradation products in water and upper sediment of two urban rivers in Shenzhen, China - Yunlang Liu; Zuoming Xie; Tingting Zhu; Chen Deng; XiuJuan Qi; Rong Hu; Jinglin Wang; Jianyi Chen (Environmental Science and Pollution Research, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Comparison of nominal and standardized catch per unit effort data in quantifying habitat suitability of skipjack tuna in the equatorial Pacific Ocean - Cheng Zhou; Yuanyuan Hu; Jie Cao; Liuxiong Xu; Xuefang Wang; Rong Wan; Yu Xiao; Jiangfeng Zhu; Hao Tang (Acta Oceanologica Sinica, 2022)

Mystery of methamphetamine-induced autophagosome accumulation in hippocampal neurons: loss of syntaxin 17 in defects of dynein–dynactin driving and autophagosome–late endosome/lysosome fusion - Huaisha Xu; Yuanhui Zhu; Xufeng Chen; Tingyu Yang; Xi Wang; Xu Song; Xuexue Xie; Miaoyang Hu; Lei Jiang; Jie Cheng; Rong Gao; Jun Wang (Archives of Toxicology, 2021)

Deletion of Nrip1 delays skin aging by reducing adipose-derived mesenchymal stem cells (ADMSCs) senescence, and maintaining ADMSCs quiescence - Yu Hu; Yun Zhu; Skyler D. Gerber; Jared M. Osland; Min Chen; Krishna A. Rao; Heng Gu; Rong Yuan (GeroScience, 2021)

Late Cretaceous granitic magmatism and Sn mineralization in the giant Yinyan porphyry tin deposit, South China: constraints from zircon and cassiterite U–Pb and molybdenite Re–Os geochronology - Peng-Cheng Hu; Wei-Guang Zhu; Hong Zhong; Rong-Qing Zhang; Xiao-Yu Zhao; Wei Mao (Mineralium Deposita, 2021)

Influence of the roots of mixed-planting species on the shear strength of saline loess soil - Ya-bin Liu; Xia-song Hu; Dong-mei Yu; Hai-li Zhu; Guo-rong Li (Journal of Mountain Science, 2021)

A New Record of Oxytricha granulifera granulifera Foissner and Adam, 1983 (Protozoa, Ciliophora, Oxytrichidae) From a Hot Spring in Iceland, With Notes on Its Abnormal Form During Cultivation - Rong Zhu; Zhishuai Qu; Qi Zhang; Sabine Filker; Thorsten Stoeck; Fengchao Li; Xiaozhong Hu (Frontiers in Marine Science, 2021)
We isolated a population of Oxytricha granulifera granulifera Foissner and Adam (1983) from a hot spring in Iceland. The pure culture of this isolate was established at room temperature in the laboratory. This allowed for a detailed investigation, informed by integrated approaches, of the isolate’s morphology and morphogenesis, as well as molecular phylogeny. Results showed that the morphological and morphogenetic characteristics of the Iceland population are consistent with those of other populations. During the 3-year long period of laboratory cultivation, some abnormal individuals appeared repeatedly in the culture system. Interestingly, the morphological characteristics of these abnormal cells were rather stable, and were as follows: 1) body slender and elliptical-shaped; 2) remarkably shortened adoral zone and significantly reduced number of adoral membranelles; and 3) loss of undulating membranes. Resting cysts, binary fission and conjugate reproduction were not found in abnormal specimens. Although the morphology of abnormal individuals changed significantly, the sequences of the SSU rDNA of the normal and abnormal morphotypes were the same. Phylogenetic analyses showed that the two morphotypes clustered in a clade with other populations of O. granulifera granulifera .

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

An integrated prevention strategy to address problems associated with continuous cropping of watermelon caused by Fusarium oxysporum - Fu-Yan Liu; Qiang Zhu; Hu-Rong Yang; Jun Zhou; Chuan-Chao Dai; Xing-Xiang Wang (European Journal of Plant Pathology, 2019)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

Characterization and Cu sorption properties of humic acid from the decomposition of rice straw - Yongbo Qi; Jun Zhu; Qingling Fu; Hongqing Hu; Xingmin Rong; Qiaoyun Huang (Environmental Science and Pollution Research, 2017)

Asymmetric evolution of El Niño and La Niña: the recharge/discharge processes and role of the off-equatorial sea surface height anomaly - Zeng-Zhen Hu; Arun Kumar; Bohua Huang; Jieshun Zhu; Rong-Hua Zhang; Fei-Fei Jin (Climate Dynamics, 2017)

Erratum to: The Extent of Heavy Metal Pollution and Their Potential Health Risk in Topsoils of the Massively Urbanized District of Shanghai - Syed Taseer Abbas Jaffar; Fan Luo; Rong Ye; Hassan Younas; Xue-feng Hu; Long-zhu Chen (Archives of Environmental Contamination and Toxicology, 2017)

The Extent of Heavy Metal Pollution and Their Potential Health Risk in Topsoils of the Massively Urbanized District of Shanghai - Syed Taseer Abbas Jaffar; Fan Luo; Rong Ye; Hassan Younas; Xue-feng Hu; Long-zhu Chen (Archives of Environmental Contamination and Toxicology, 2017)

Chlorophyll fluorescence lifetime imaging provides new insight into the chlorosis induced by plant virus infection - Rong Lei; Hongshan Jiang; Fan Hu; Jin Yan; Shuifang Zhu (Plant Cell Reports, 2017)

Pseudomonas syringae pv. Actinidiae isolated from non-kiwifruit plant species in China - Pu Liu; Shizhou Xue; Rong He; Jiayong Hu; Xiaojie Wang; Bing Jia; Lorenzo Gallipoli; Angelo Mazzaglia; Giorgio M. Balestra; Liwu Zhu (European Journal of Plant Pathology, 2016)

The influence of plant root system architectural properties upon the stability of loess hillslopes, Northeast Qinghai, China - Jiang-tao Fu; Xia-song Hu; Gary Brierley; Na Qiao; Qin-qin Yu; Hai-jing Lu; Guo-rong Li; Hai-li Zhu (Journal of Mountain Science, 2016)

Immunosuppressive Effect of Hypodermin C on Complement Component 3 In Vitro - An-Kang Hu; Ren-Jin Chen; Xiao-Rong Zhu; Jian-Hong Gu; Zong-Ping Liu (Cell Biochemistry and Biophysics, 2015)

The anti-angiogenic role of discoidin domain receptor 2 (DDR2) in laser-induced choroidal neovascularization - Tong Zhu; Jie Zhu; Xin Bu; Hu Zhao; Shuya Zhang; Yuan Chang; Rong Li; Libo Yao; Yusheng Wang; Jin Su (Journal of Molecular Medicine, 2015)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

Calreticulin is localized at mitochondria of rat cardiomyocytes and affected by furazolidone - Hu Shan; Jin Wei; Ming Zhang; Lin Lin; Rui Yan; Yanhe Zhu; Rong Zhang (Molecular and Cellular Biochemistry, 2014)

Systemic Evaluation of Hypoxic-Ischemic Brain Injury in Neonatal Rats - Ai-Hua Zhu; Yan-Rong Hu; Wei Liu; Feng Gao; Jian-Xin Li; Li-Hui Zhao; Gang Chen (Cell Biochemistry and Biophysics, 2014)

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Expression, purification, and activity assay of peptide deformylase from Escherichia coli and Staphylococcus aureus - Xuchun Che; Jinwei Hu; Lijuan Wang; Zhifeng Zhu; Qiong Xu; Junqiang Lv; Zheng Fu; Yajun Sun; Jia Sun; Gang Lin; Rong Lu; Zhi Yao (Molecular and Cellular Biochemistry, 2011)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Proteiomic patterns for endometrial cancer using SELDI-TOF-MS - Li-rong Zhu; Wen-ying Zhang; Li Yu; Yan-hua Zheng; Jun Hu; Qin-ping LIAO (Journal of Zhejiang University-SCIENCE B, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Autotoxic potential of cucurbit crops - Jing Quan Yu; Sen Yan Shou; Ya Rong Qian; Zhu Jun Zhu; Wen Hai Hu (Plant and Soil, 2000)